Kualitas Pelayanan Penyediaan Air Bersih Pada Perusahaan Daerah Air Minum (PDAM) Di Kota Bengkulu (Penelitian Di PDAM Tirta Hidayah Kota Bengkulu) - Purwanti, Tri (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to determine the quality of clean water services at the Tirta Hidayah Regional Drinking Water Company (PDAM) in Bengkulu City and to determine what inhibiting and supporting factors are experienced by the Tirta Hidayah Regional Drinking Water Company (PDAM) in providing services to its customers in Bengkulu City. The method used by the researcher, namely qualitative research, is a method for exploring and understanding the meaning that a number of individuals or groups of people consider to come from social or humanitarian problems. The results of the study are: The Quality of Service at the Tirta Hidayah Regional Drinking Water Company (PDAM) in Bengkulu City, in terms of tangibility, is included in the good category, because of the completeness of the facilities and infrastructure in the company. Service Quality at the Regional Drinking Water Company (PDAM) Tirta Hidayah, Bengkulu City, seen from the reliability aspect, is included in the good category, because the employees are very reliable in providing services, Service Quality at the Regional Drinking Water Company (PDAM) Tirta Hidayah, Bengkulu City, seen from the responsiveness aspect, is included in the good category, because when responding to customers they are good with customers, Service Quality at the Regional Drinking Water Company (PDAM) Tirta Hidayah, Bengkulu City, seen from the assurance aspect, is included in the good category, because PDAM provides a guarantee of comfort in serving its customers, Service Quality at the Regional Drinking Water Company (PDAM) Tirta Hidayah, Bengkulu City, seen from empathy, is included in the good category. Because these employees really care about customers when there is a problem. Suggestions for employees whose level of service quality in serving the community should be given rewards/awards so that other employees are more enthusiastic in providing services and the Regional Drinking Water Company of Bengkulu City should improve in providing counseling and information as well as socialization. Research limitations based on the researcher's experience during the research, the researcher realized that the results of this study were not perfect and had many limitations that affected the expected results, one of which was the number of samples processed in this study, which was only 30 respondents because in PDAM users in Bengkulu City, many were divided into 3 zones when conducting research in the field, many did not use PDAM and many disconnected PDAM..